Efficacy and Toxicity of Stereotactic Radiotherapy Using CyberKnife in Patients of Meningioma: A Single Institutional Study - Shabbir, Saima Madiha; Mahmood, Humera (Biological and Clinical Sciences Research Journal, 2025)
Meningiomas are among the most common primary intracranial tumors; while typically benign, management is challenging when lesions abut critical neurovascular structures. Stereotactic radiotherapy (SRT) with the CyberKnife® system provides a non-invasive, highly conformal alternative to surgery. Objective: To evaluate the efficacy and toxicity of CyberKnife-based stereotactic radiosurgery (SRS) and fractionated stereotactic radiotherapy (FSRT) for meningiomas treated at a single Pakistani institution. Methods: This observational descriptive study was conducted in the Department of Oncology, NORI, Islamabad, from December 2023 to December 2024 and enrolled 39 patients with WHO grade I–II or recurrent meningiomas. Treatment modality and dose were individualized by tumor size, grade, and proximity to organs at risk. SRS was delivered in a single fraction (13–18 Gy), and FSRT in 3–5 fractions (total 21.5–30 Gy), adhering to contemporary critical-structure constraints. Efficacy was assessed clinically (symptom change) and radiologically using Response Assessment in Neuro-Oncology (RANO) criteria on MRI at approximately 3, 6, and 12 months. Toxicities were recorded prospectively. Descriptive statistics (counts, percentages, medians) were used to summarize baseline characteristics, disease control, and adverse events. Results: The cohort consisted of 72.7% females, with a median age of 52 years. Common locations were parafalcine (25.6%) and cerebral convexity (20.5%). Thirteen patients received SRS and 26 received FSRT. At 6 months, radiologic disease control was achieved in 91% of patients, with stable disease in 91% and a minor radiographic response in 9%. No progressive disease was observed during follow-up. Symptomatic improvement occurred in 70% of patients with headaches and/or seizures and in 20% with focal neurological deficits. Treatment was well tolerated; transient headaches consistent with radiation-related edema were managed with short-course corticosteroids, and no clinically significant late toxicities were documented. Conclusion: CyberKnife-based SRS and FSRT provided high rates of radiologic stability and meaningful symptom relief with minimal toxicity in patients with meningioma at a Pakistani tertiary center. These findings support the effectiveness and safety of CyberKnife SRT as a practical option, including in resource-constrained settings.